The value of anti-rods and rings antibodies in patients with nonhepatitis virus infection: A single-center retrospective study from Southwest China. Issue 20 (21st May 2021) - Zhang, Naidan; Ji, Chaixia; Yang, Hao; Liu, Lihong; Bao, Xiao; Zhou, Yusha; Yuan, Chengliang
Abstract : Abstract: The aim of this study was to retrospectively investigate the clinical significance of anti-rods and rings (anti-RR) antibodies in nonhepatitis virus infection patients from Southwest China. Anti-RR antibodies were determined by indirect immunofluorescence assay in a group of 19, 935 individuals with antinuclear antibodies test from January 2017 to December 2019. The laboratory and clinical data were collected. Finally, 66 samples with anti-RR antibodies (0.33%) were detected. In Wilcoxon rank sum test, gamma glutamyl transferase ( Z = −3.364, P = .001), alpha-l-fucosidase (AFU) ( Z = −2.312, P = .021), uric acid ( Z = −1.634, P = .047) and red blood cell distribution width ( Z = −2.285, P = .022) were higher in metabolic disease group than nonmetabolic disease group. In independent-samples t test, endogenous creatinine clearance was higher in metabolic disease group than nonmetabolic disease group ( t = 2.061, P = .045). During the follow-up period of 37 patients with anti-RR antibodies for 1 to 60 months, the titers of anti-RR were significantly increased in the metabolic disease group ( Z = −2.346, P = .019). In binary logistic regression analysis, triglycerides (odds ratio 3.679, 95% confidence interval 1.467–24.779, P = .048) was associated with elevated titers of anti-RR antibodies. In summary, anti-RR in non-hepatitis patients may be a manifestation of metabolic disorders, and has a certain correlation with routine laboratory indicators, which is worthy of the attention from clinicians. Abstract : Supplemental Digital Content is available in the text